Taxonomic revision, phylogeny and conservation status of scaphochlamys (Zingiberaceae) / Sam Yen Yen - Sam, Yen Yen (2014)

(untitled)
The genus Scaphochlamys is a group of small wild gingers in the tribe Zingibereae Meisn., subfamily Zingiberoideae Haask.. The main objective of the current study is to revise the genus based on its morphological characters. In addition, it also aims to investigate the interspecific relationship, the endemism and distribution patterns and assess the conservation status of the Scaphochlamys species. The present taxonomic treatment recognises 41 species and 5 varieties which includes the addition of 10 new species; 1 species is reinstated and 2 varieties are synonymised. Likewise, 18 unknown taxa were also identified. The group is highly polymorphic with many local species found within a small distribution range. Examination on its morphology shows that there is no single character to separate the Scaphochlamys species and its closely allied genera; instead a combination of characters is used for identification. Based on the detailed morphological study, a taxonomic key has been successfully established for Scaphochlamys species. Results from the current molecular phylogenetic study confirmed that Scaphochlamys is monophyletic. A total of 31 species investigated using nuclear ribosomal ITS sequences resulted in 2 main clades which correspond with the phytogeographical regions of Malaya (Peninsular Malaysia) and Borneo. One of the clades consists of the Bornean species (except S. polyphyla) plus Myxochlamys while another clade incorporates Peninsular Malaysian and Peninsular Thailand species. The genus Scaphochlamys is distributed in the tropical evergreen rainforest of West Malesian region, from Peninsular Thailand, through Peninsular Malaysia to northern Borneo and central Sumatra. The genus is most diverse and highly endemic in Peninsular Malaysia where 70 % (29 species) of the species are found here and 27 of them are endemics. Peninsular Thailand has 5 species of which 3 are endemics and 2 are also found in Peninsular Malaysia. There are 9 species in Borneo and all are endemics while Sumatra has 1 undescribed species. The distribution pattern of Scaphochlamys has a very strong Riau Pocket element with high diversity observed in Terengganu, southeast Johor and northwest Sarawak. Results from the phytogeographical and phylogenetic analyses suggest a pre-Pleistocene migration for the lineage of Scaphochlamys and its closely allied genera. The genus is highly endangered with 59% of the taxa listed in the threatened categories: 5 taxa are Critically Endangered, 18 taxa are Endangered and 3 are Vulnerable. The endangerment is mainly due to their narrow distribution and occurrence in the production forest of the Permanent Reserved Forest network, where the potential threats in the form of habitat loss and continuing decline in the quality of habitat arising from harvesting practices are projected in the future.